Knowledge, Attitude and Practice Perceived by Nurses toward Incident Reporting in Songklanagarind Hospital - แสงมณี วัชรีย์; วัฒนสิทธิ์ ยุพิณ; แก้ววิชิต น้ำทิพย์ (Princess of Naradhiwas University Journal, 2018)
The purposes of this descriptive research were to: 1) describe knowledge, attitude, and practice as perceived by nurses toward incident reporting in Songklanagarind Hospital, and 2) examine the correlations among those three variables. Bloom’s taxonomy was used as a framework for the study. The research population was determined by the Taro Yamane’s sample size. Sample was 297 nurses who had at least 6 months of experience working in Songklanagarind Hospital. Purposive sampling was applied. Data were collected from April to July, 2017. Research instrument was a questionnaire divided into four parts including demographic data, knowledge, attitude, and practice regarding incident reporting. Reliability of the questionnaire aboutknowledge was tested using Kuder-Richardson, and yielding value of .76. Reliability of the questionnaire about attitude, and practice were tested using Cronbach’s alpha, and yielding values of .72 and .80, respectively. Statistical analyses used were descriptive statistics and Pearson product moment correlation. Results showed the average score of nurses’ knowledge, attitude, and practice perceived toward incident reporting in Songklanagarind Hospital were at a high level ( =11.33, S.D.=1.67; 4.00, S.D.= 0.43; =3.45, S.D.=0.38, respectively). There was a significant correlation between attitude and practice as perceived by the nurses (r = .28, p < .01). The findings of this study suggest that the hospital administrator should run activities to promote attitude as well as set a guideline for incident reporting continually among hospital personnel.